Is periprostatic nerve block a gold standard in case of transrectal ultrasound-guided prostate biopsy? - Kumar, Ashok (Medknow Publications & Media Pvt Ltd, 2013)
INTRODUCTION: Controversy exists over the pain during prostate biopsy. Periprostatic nerve block (PNB) is a gold standard anesthetic technique during transrectal ultrasound (TRUS)-guided prostate biopsy. Recent studies showed that PNB alone is insufficient as analgesic. We compared the efficacy of tramadol and intraprostatic nerve block (INB) in addition to PNB. MATERIALS AND METHODS: We conducted a prospective double blinded placebo controlled study at our institute in 150 consecutive patients. Patients were randomized into three groups. Group A received PNB with INB with 1% lignocaine. Group B received oral tramadol with PNB. Group C patients were administered PNB only with 1% lignocaine. Patients were asked to grade the pain level using 11 point linear visual analog scale (VAS) at the time of ultrasound probe insertion, at time of anesthesia, during biopsy, and 30 min after biopsy. RESULTS: The study groups were comparable in demographic profile, prostate-specific antigen (PSA) levels, and prostate size. Group A recorded the minimum mean pain score of 2.66 during prostate biopsy which was significantly lower than group 3 (P < 0.001). Group B recorded significantly lower pain score at time of probe insertion and at anesthetic needle insertion than other two groups. CONCLUSIONS: PNB provides better pain control in TRUS-guided prostate biopsy but still there is need of additional analgesic in the form of tramadol or INB. Tramadol has advantage of oral intake and analgesic effect at time of probe insertion and at nerve block. Both tramadol and INB may be used in combination along with PNB.